Further Investigation into the Formation Mechanism of Ash Cenospheres from an Australian Coal-Fired Power Station - Li, Yi; Gao, Xiangpeng; Wu, Hongwei (American Chemical Society, 2013)
This study continues the investigation into the ash cenosphere formation mechanism using a series of narrow size-fractioned ash cenosphere samples separated from the fly ash of an Australian coal-fired power station. The gas products locked inside various ash cenosphere size fractions are dominantly CO2 and some N2. With increasing ash cenosphere particle size from 63–75 μm to 150–250 μm, the average gas pressure decreases from 0.227 atm (at normal temperature and pressure, NTP) to 0.172 atm while the amount of CO2 and N2 locked in ash cenospheres increases significantly. The SiO2/Al2O3 ratio decreases with increasing ash cenosphere size, accompanied with an increase in the sum of TiO2 and Fe2O3 contents. Thermomechanical analysis further shows that ash cenospheres of different size fractions cannot achieve full melting at 1600 °C, suggesting that the formation of these ash cenospheres requires higher temperatures. Further analysis based on ash chemistry of individual cenospheres suggests that the optimum particle temperature for cenosphere formation is ~1640–1850 °C. The growth of cenosphere precursors is governed by a wide range of viscosity of molten cenosphere precursors together with the force of surface tension, which is inversely proportional to the viscosity of molten droplets, producing ash cenospheres with various wall thicknesses. The data suggest that, apart from Fe2O3, TiO2 may play an important role in the formation of ash cenospheres.